RELATIONSHIP OF PARENTING TO PERSONAL HYGIENE INDEPENDENT OF PRE SCHOOL IN DHARMA WANITA KINDERGARTEN, JATIREJO MOJOKERTO - Tria Wahyu Ningrum; Tri Ratnaningsih; Siti Mas Miranda (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Currently, many children of school age are lacking in hygiene themselves so as to facilitate the occurrence of diseases such as diarrhea or intestinal worms. This situation occurs because the child is not yet able to perform personal hygiene independently or still assisted by parents. The purpose of the research to know the relationship of parenting pattern with preschool children hygiene personal independent. Design of this research was analytic correlational with crossectional approach. Research variables were parenting pattern as the independent variable and independent personal hygiene as the dependent variable. Population research was all of the parents who have children in kindergarten preschool age of Dharma Wanita Jatirejo Mojokerto. Samples were taken with the technique of total sampling as much as 45 respondents. Data collected by questionnaire sheet and tested with a test of chi-square. The results showed that respondents from 16 to apply democratic parenting most of self-reliance, personal hygiene of children in independent category as much as 9 respondents (20.0%), of the 16 respondents who applied the authoritarian parenting there are no independent and children from parents who apply the permissive parenting most of the children belonged to independent as much as 5 respondents (11.1%). The chi-square test results obtained the value of Ï = 0, 006 and Î± = 0.05 so Ï Î± there is relationship < parenting parents against independent, personal hygiene for children. This shows the more appropriate parenting adopted parents will further improve the independent of the personal hygiene of preschool age children. Give a freedom to children do make children become easy to do some useful thingParenting adopted by parents in educating children will give impact on the child's independent and personality s for her future, but in the absence of parental control, in fact, will make children become unruly. Key Words : Parenting, Personal Hygiene Independent, Preschool Children